An Evaluation of Boarding School Curriculum Implementation in Aceh - Herman, Herman; Rohana, Sy.; Jailani, Jailani (Graduate Program Magister Manajemen Pendidikan, 2024)
The purpose of this article is to evaluate the implementation of the boarding school curriculum at MTsS Nurul Falah, West Aceh Regency. This article uses the CIPP (Context-Input-Process-Product) model evaluation method developed by Stufflebeam. Data collection techniques are carried out through observation, questionnaires, interviews and document studies related to the boarding school curriculum. Data analysis uses the opinion of Miles and Haberman, namely data reduction, data display, drawing conclusions and data verification. The research results indicate that the implementation of the boarding school curriculum at MTsS Nurul Falah in West Aceh District has been running well and in accordance with the standard set by the foundation and the government. In the future, to bring forth new innovations in implementing the boarding school curriculum, there is a need for continuous guidance and specialized training for the teachers of dayah/boarding schools to optimize the quality of the learning process and the educational outcomes. The results of this study can provide input for the headmasters of madrasahs and the heads of the Ministry of Religious Affairs offices in making decisions related to improving the quality of education.